1994
DOI: 10.1002/jmv.1890440406
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of enterovirus outbreaks in Canada during 1991–1992: Identification of echovirus 30 and coxsackievirus B1 strains by amplicon sequencing

Abstract: The relatedness of enteroviral isolates associated with two recent outbreaks in Canada was assessed using direct sequencing of amplicons derived from a large portion of the 5' nontranslated region (NTR) of the viral genome. The amplicons of 60 echovirus 30 isolates originating from seven different provinces in 1991 were found to share 99% or greater sequence identity. Recent coxsackievirus B1 isolates characterised in the same manner were identical to each other. When the 5' NTR sequence of these isolates was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…This is also important to help increasing the accuracy of clinical diagnosis, eliminating unnecessary laboratory tests [Drebot et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…This is also important to help increasing the accuracy of clinical diagnosis, eliminating unnecessary laboratory tests [Drebot et al, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…Biotinylated nested-PCR products were sequenced using a direct solid-phase T7-polymerase-mediated nucleotide sequencing strategy, using either a fluorescein-labelled sequencing primer for analysis with an ALF automated DNA sequencer (Pharmacia) as described previously by Nicholson et al (1995), or an unlabelled sequencing primer and Dyedeoxy terminators (Applied Biosystems) for analysis with a 373 automated DNA sequencer (Applied Biosystems). Sequences thus derived were compared with published enterovirus sequences (Chang et al, 1989;Drebot et al, 1994;Hughes et al, 1989;Dahllund e~ al., 1995;Iizuka et al, 1987;Jenkins et al, 1987;Klump et al, 1990;Kraus et al, 1995;Lindberg et al, 1987;Pulli et al, 1995;P6yry et al, 1994;Romero & Rotbart, 1995;Ryan et al, 1990;Supanaranond et al, 1992;Toyoda et al, 1984;Zhang et at., 1993;Zheng et al, 1995), using DNASIS to estabish the likely serotypic identity of viruses detected by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7] In China, outbreaks of aseptic meningitis associated with E30 have been sequentially reported in Jiangsu and Shandong in recent years. 8,9 In our prior study, we found that E30 was the predominant serotype in enterovirus-associated encephalitis from 2010 to 2012.…”
Section: Introductionmentioning
confidence: 99%